Effect of eugenol treatment in hyperglycemic murine models: A meta-analysis. (March 2021) - Carvalho, Renner Philipe Rodrigues; Lima, Graziela Domingues de Almeida; Machado-Neves, Mariana
Graphical abstract: Abstract: Diabetes is a highly prevalent health condition affecting many people worldwide. In vitro studies have described the positive effects of cloves and its major compound, eugenol, in the treatment of diabetes. However, it is unclear whether the effects of this compound are negative, neutral, or positive, on hyperglycemic animals. Therefore, a meta-analytical review was conducted to determine the magnitude of effects of eugenol on variables directly and indirectly related to diabetes. This study revealed that eugenol treatment decreased the glucose levels and the activity of carbohydrate-metabolizing enzymes, ameliorated the lipid profile, and reduced the oxidative, renal, and hepatic damages in hyperglycemic rodents. Moreover, eugenol alleviated the weight loss and restored the activity of the antioxidant defense system. Insulin levels was not affected by eugenol treatment. Also, mixed model analyses revealed that the use of purified or non-purified eugenol and the concentrations administered significantly affected the treatment outcome. In conclusion, our findings indicate that eugenol may have potential therapeutic effects in the treatment of diabetes. Furthermore, this study can direct future preclinical and clinical trials, with important implications for human health.